Cyperus spp.: A Review on Phytochemical Composition, Biological Activity, and Health-Promoting Effects. (8th September 2021) - Taheri, Yasaman; Herrera-Bravo, Jesús; Huala, Luis; Salazar, Luis A.; Sharifi-Rad, Javad; Akram, Muhammad; Shahzad, Khuram; Melgar-Lalanne, Guiomar; Baghalpour, Navid; Tamimi, Katayoun; Mahroo-Bakhtiyari, Javad; Kregiel, Dorota; et al.
Abstract : Cyperaceae are a plant family of grass-like monocots, comprising 5600 species with a cosmopolitan distribution in temperate and tropical regions. Phytochemically, Cyperus is one of the most promising health supplementing genera of the Cyperaceae family, housing ≈950 species, with Cyperus rotundus L. being the most reported species in pharmacological studies. The traditional uses of Cyperus spp. have been reported against various diseases, viz., gastrointestinal and respiratory affections, blood disorders, menstrual irregularities, and inflammatory diseases. Cyperus spp. are known to contain a plethora of bioactive compounds such as α -cyperone, α -corymbolol, α -pinene, caryophyllene oxide, cyperotundone, germacrene D, mustakone, and zierone, which impart pharmacological properties to its extract. Therefore, Cyperus sp. extracts were preclinically studied and reported to possess antioxidant, anti-inflammatory, antimicrobial, anticancer, neuroprotective, antidepressive, antiarthritic, antiobesity, vasodilator, spasmolytic, bronchodilator, and estrogenic biofunctionalities. Nonetheless, conclusive evidence is still sparse regarding its clinical applications on human diseases. Further studies focused on toxicity data and risk assessment are needed to elucidate its safe and effective application. Moreover, detailed structure-activity studies also need time to explore the candidature of Cyperus -derived phytochemicals as upcoming drugs in pharmaceuticals.